Synoptic changes in the deep rim current during stagnant hydrographic conditions in the Eastern Gotland Basin, Baltic Sea - Eberhard Hagen; Rainer Feistel (Oceanologia, 2007)
Hydrographic and current measurements are analysed for stagnantdeep-water conditions over the south-eastern topographic flankof the Eastern Gotland Basin (EGB) in April 2000.Results suggest a prevailing barotropic motion mode on a synopticscale of several days. Deep along-slope volume transports derivedfrom subsurface current meter moorings are compared with thoseof the baroclinic fraction of geostrophic motions crossing theplane of a hydrographic section. This was aligned perpendicularto deep isobaths and was repeated 40 times with a time step ofsix hours. Changes in regional winds produced a quasi-ten daycycle in the filling level of the Baltic Proper. Associated wave-likefluctuations of the mass field propagated cyclonically with avelocity of about 0.04 m s-1 around the deep basin's rim. Itis concluded that associated changes in deep volume transportsresult mainly from barotropically governed advection processesand that those of the baroclinic component of geostrophic currentsprovide a qualitatively and quantitatively quite inaccurate descriptionof related transport fluctuations on a daily scale.